The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/ddi.13149
|View full text |Cite
|
Sign up to set email alerts
|

Using modelled prey to predict the distribution of a highly mobile marine mammal

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 65 publications
(103 reference statements)
0
18
0
Order By: Relevance
“…with low associated measurement error, unlike remote sensed or modelled variables which may help improving the explanatory power of the models. Pendleton et al [79] observed similar results for bowhead whales (Balaena mysticetus). They compared a model using only environmental and biological variables such as sea ice thickness, sea temperature, diatoms, flagellates, copepods and zooplankton from the Biology Ice Ocean Modeling and Assimilation System (BIO-MAS) to a model using these variables plus bathymetry and showed that the best model included bathymetry and BIOMAS variables.…”
Section: Ability Of Seapodym and Environmental Variables To Model Deep-diver Distributionsmentioning
confidence: 63%
“…with low associated measurement error, unlike remote sensed or modelled variables which may help improving the explanatory power of the models. Pendleton et al [79] observed similar results for bowhead whales (Balaena mysticetus). They compared a model using only environmental and biological variables such as sea ice thickness, sea temperature, diatoms, flagellates, copepods and zooplankton from the Biology Ice Ocean Modeling and Assimilation System (BIO-MAS) to a model using these variables plus bathymetry and showed that the best model included bathymetry and BIOMAS variables.…”
Section: Ability Of Seapodym and Environmental Variables To Model Deep-diver Distributionsmentioning
confidence: 63%
“…Such changes have clear bioenergetic implications for marine mammals and the ecosystems they inhabit ( Costa, 2008 ; Laidre et al, 2020 ; Gallagher et al, 2022 ). Since the prey landscape is a major driver of the spatiotemporal distribution of marine mammals ( Sveegaard et al, 2012 ; Zerbini et al, 2016 ; Sigler et al, 2017 ; Straley et al, 2018 ; Pendleton et al, 2020 ), knowledge of prey fields and how they may be changing provides insight into the potential impact of anthropogenic disturbances on energy budgets ( Keen et al, 2021 ). As such, prey fields are critical components of many PCoD models ( Nabe-Nielsen et al, 2018 ; Pirotta et al, 2019 ; McHuron et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…This methodology has been applied solely to Auk species using the Barents Sea as a closed domain; however, it could also be applied to other species and other regions, including vulnerable marine mammals such as Baleen Whales, Ross Seals ( Ommatophoca rossi ) and dolphins in the Southern Ocean: several previous studies have demonstrated the importance of ocean thermal conditions to these species when seeking prey at depth by using MaxENT to model their occupancy ranges (El‐Gabbas et al., 2021; Pendleton et al., 2020; Wege et al., 2021). These studies also benefit from the use of multiple environment variables which is not the case for this study (see Skov et al.…”
Section: Discussionmentioning
confidence: 99%